NAMPT regulates mitochondria and oxidative stress level for mouse early embryo development - Mei-Hua Liao; Xin Liu; Xiao-Ting Yu; Shun Zhang; You-Zhu Li; Lin-Lin Hu; Shao-Chen Sun; Jun-Li Wang (Biological Research)
Abstract Background Nicotinamide phosphoribosyltransferase (NAMPT) is an enzyme that involves into NMN-NAD + synthesis which involves into cellular metabolism related with aging, immune function, and neurodegeneration. However, its roles in early embryo development are still unclear. Methods In present study we disturbed the NAMPT activity and employed immunofluorescence staining and live cell imaging to explore its roles during early embryo development. Results We showed that NAMPT mRNA level was stable during mouse early embryo development, and NAMPT accumulated in the nucleus of blastomeres in mouse embryos. The loss of NAMPT activity disturbed the early cleavage from zygote to 2-cell, 4-cell to morula formation in the dose-dependent manner. We found that NAMPT inhibition disrupted mitochondria function in 2-cell embryos, showing decreased mitochondria number and aberrant accumulation in the blastomeres, which further disturb mitochondrial membrane potential level and elevated ROS level in embryos, indicating the occurrence of oxidative stress. Moreover, NAMPT inhibition also increased the apoptotic index, showing with increased Annexin-V signals and apoptotic gene expression. Conclusions Taken together, our study provided the evidence that NAMPT was essential for the mitochondria function to control oxidative stress and apoptosis during mouse early embryo development.